THE 21st-CENTURY SKILLS REPRESENTED IN READING TASKS OF JUNIOR HIGH SCHOOL ENGLISH TEXTBOOKS - Sintya Wulandari; Hendi Hidayat (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
The purpose of this research is to reveal the representation of the 21st-century skills in the reading tasks of junior high school English textbooks for grade VIII and compare the results of data between the textbook published by Erlangga publishing and the textbook published by the The Ministry of Education and Culture. The integration of the 21st-century skills in English textbook is important for students to deal with globalization. Using the descriptive qualitative method and content analysis, this research analyzed the representation of the 21st-century skills in reading tasks of Junior High School English textbooks “Bright an English” published by Erlangga and the textbook “When English Rings a Bells” published by The Ministry of Education and Culture for grade VIII for Junior High School based on the categories of 12 competencies from the framework for 21st-century learning. As a result, the researcher found that there were slightly different results from two English textbooks. Textbook 1 refers to the “Bright an English” textbook presents 9 skills. Meanwhile, textbook 2 refers to “When English Rings a Bells” textbook presents 8 skills which had fewer than textbook 1. The textbooks use the 2013 English curriculum materials. It also has fulfilled the criteria of a good textbook. This research definitively answers the question regarding the representation of 21st-century skills in the reading task of Junior High School English textbooks.